Healer Reception of Jesus as healer during Early Christianity and Today - Dube, Zorodzai (HTS Religion & Society Series, 2020)
This book explores the established field of healing narratives in the New Testament by focusing on the remembered tradition regarding Jesus' healings and comparing them with those of other healers, such as Asclepius. A sub-theme to the book is to investigate the reception of Jesus as healer in various African communities. The book exposes the various healing methods employed by Jesus such as exorcism, touch and the use of spittle. Like any other healing performances that reflect the healthcare system of a given culture, Jesus' healings were holistic: healing the bodily pain, restoring households and combatting stigmatisation and marginalisation. The book demonstrates Jesus' healing activities as "shalom" performances that seek to re-establish peace in all its social dimensions. With regard to the reception of Jesus as healer in the African context, the book elaborates the sacrificial lamb motif and the need for restoring a relationship with God. All the contributions in the book present a unique and original perspective in understanding Jesus as healer from an African healthcare system.